Digital Divide: A Comparison of Undergraduate Female Student’s Use of Social Media Platforms in Urban and Rural - R, Nivetha; B. Radha (Indian Journal of Educational Technology, 2024)
The Covid-19 pandemic has contributed to the increase in online education and subsequent social media use among the student communities globally. The use has drastically changed the everyday life patterns concerned with their education, communication, and entertainment needs. Research shows that social media platforms provide formal and informal learning opportunities influencing higher education. They offer a space for collaborative learning, sharing, and communicating with not only friends but also teachers. However, access and use vary among student communities based on gender, class, nationality, and language. Understanding students' experiences using social media platforms is vital beyond the barriers mentioned above. In the given context, the study contributes to understanding female students’ engagement and participation with social media platforms. It tries to determine if there are differences in access use and purpose of use of social media platforms among urban and rural women students. This study identifies the digital divide in terms of urban-rural and locates the need to empower rural female students by requiring knowledge and skills as part of their educational curriculum in higher education institutions.